Vestibular dysfunction and postural balance in cochlear implant users: a narrative literature review - Melo,Juliana Jandre (2018)
ABSTRACT Cochlear implants directly stimulate nerve fibers and ganglion cells of the auditory nerve, which transform sound energy into low levels of electrical current, stimulating the remaining fibers of the auditory nerve in patients with severe to profound hearing loss, in order to provide the significant range of auditory sensation and speech comprehension. Due to the close relationship between cochlea and vestibular receptors, some patients may present vestibular and postural balance changes concomitantly after surgery. This study aimed to perform a narrative review of the main studies that relate vestibular symptoms in patients implanted in the last six years. The research was performed through the databases: SciELO, LILACS and PubMed, using associated descriptors for "cochlear implant", "vestibular dysfunction", "vertigo" and "balance", totalizing 21 studies that fitted the inclusion criteria. The results were described in a chronological order of publication, showing the main conclusions. Of the total studies analyzed, 18 related vestibular function to cochlear implant and only 3 studies did not find such a relationship. The literature characterize the effects of the cochlear implant on the vestibular system, however, the results are contradictory.